Where is Industry Getting it Wrong? A Review of Quality Concerns Raised at Day 120 by the Committee for Medicinal Products for Human Use during European Centralised Marketing Authorisation Submissions for Chemical Entity Medicinal Products - John Joseph Borg; Jean-Louis Robert; George Wade; George Aislaitner; Michal Pirozynski; Eric Abadie; Tomas Salmonson; Patricia Vella Bonanno (Frontiers Media S.A., 2009)
ABSTRACT - Purpose. The aim of this study was to identify common trends in the deficiencies identified in the quality part of the dossier during the evaluation of marketing authorisation applications for medicinal products for human use submitted through the EU's centralised procedure. Methods. We analysed all the adopted Day 120 list of questions on the quality module of 52 marketing authorisation applications for chemical entity medicinal products submitted to the European Medicines Agency and evaluated by the Committee for Medicinal Products for Human Use (CHMP), during 12 consecutive plenary meetings held in 2007 and 2008. Subsequently we calculated the frequency of common deficiencies identified across these applications. Results. Frequencies and trends on quality deficiencies have been recorded and presented for 52 marketing authorisation applications. 32 "Major Objections" originated from 13 marketing authorisation applications. 13 concerned were raised regarding drug substances and 19 for drug products. Furthermore, 905 concerns on drug substance and 1,054 on drug product were also adopted. Conclusions. The impact of the frequencies and trends in quality deficiencies that were identified are discussed from a regulatory point of view. It is expected that the results of this study will not only be of interest to pharmaceutical companies but will also aid regulators' in obtaining consistent information on drug products based on transparent rules safeguarding the necessary pharmaceutical quality of medicinal products.